2009
DOI: 10.1371/journal.pone.0005287
|View full text |Cite
|
Sign up to set email alerts
|

CD45RC Isoform Expression Identifies Functionally Distinct T Cell Subsets Differentially Distributed between Healthy Individuals and AAV Patients

Abstract: In animal models of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), the proportion of CD45RC T cell subsets is important for disease susceptibility. Their human counterparts are, however, functionally ill defined. In this report, we studied their distribution in healthy controls (HC), AAV patients and in Systemic lupus erythematous (SLE) patients as disease controls. We showed that CD45RC expression level on human CD4 and CD8 T cells identifies subsets that are highly variable among in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…In humans, Saoudi and colleagues described that human CD45RC high and CD45RC low/-T cells were able to secrete Th1 and Th2 cytokines, respectively, similarly to that observed in rats (10). In addition, the same group described a poor prognosis and a higher risk of acute rejection for kidney transplant patients exhibiting more than 54.7% of CD8 + CD45RC…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In humans, Saoudi and colleagues described that human CD45RC high and CD45RC low/-T cells were able to secrete Th1 and Th2 cytokines, respectively, similarly to that observed in rats (10). In addition, the same group described a poor prognosis and a higher risk of acute rejection for kidney transplant patients exhibiting more than 54.7% of CD8 + CD45RC…”
Section: Discussionmentioning
confidence: 68%
“…In humans, a high proportion of CD45RC high CD8 + T cells before transplantation has been correlated with decreased graft survival in kidney transplanted patients (25). The subset of human T cells expressing CD45RC exhibits cytokine profiles after polyclonal stimulation, similarly to rats (10).…”
Section: Rat and Human Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of Th17 cells reactive to the autoantigen PR3 was found to be increased in patients with GPA in remission [88•, 113]. Furthermore, Ordonez et al found that AAV patients have an expanded CD45RC-positive T helper cell population that is a source of IL-17 [114]. IL-17 acts on endothelial cells, epithelial cells, and antigen-presenting cells, causing release of chemokines that will activate neutrophils, for example IL-8 and CXCL-1 [115].…”
Section: Role Of B and T Lymphocytesmentioning
confidence: 99%
“…CD45RC has been shown in rats, mice, and humans to be a marker of both CD4 + and CD8 + Tregs (15)(16)(17)(18)(19)(20). In a rat cardiac allograft model, we have previously shown that blockade of CD40-CD40L interaction by CD40Ig treatment induces longterm allograft survival through the generation of CD8 lo Tregs, which do not inhibit cardiac allograft rejection (18).…”
Section: Introductionmentioning
confidence: 99%